Institutional Authority Reconstruction in Anti-Corruption Enforcement: An Islamic Legal Approach to SDG 16 - Fadly Hasibuan, Muhammad; Febrian; Iza Rumesten RS; Saifudin Amin (Profetika: Jurnal Studi Islam, 2025)
Objective: This study aims to analyze the authority of law enforcement agencies in handling corruption crimes in Indonesia and its relationship with efforts to realize the effectiveness of law enforcement that supports the achievement of SDG 16 on justice and transparent governance. Theoretical framework: The theoretical framework of this research is based on the concept of the authority of law enforcement agencies in the eradication of corruption by examining the applicable legal basis and the idea of reconstructing the ideal law enforcement system, including the perspective of national criminal law and Islamic criminal law. Literature review: A literature review discusses the regulations governing the authority of investigation, investigation, and prosecution by law enforcement agencies in corruption cases, as well as the ideal concept of law enforcement in the eradication of corruption. Methods: This study uses a normative juridical method through a literature study of laws and regulations and legal references to analyze the insynchronization of authority between law enforcement agencies. Results: The results of the study show that there is an overlap of authority between law enforcement agencies that causes institutional conflicts, delays in handling cases, as well as potential political intervention and legal uncertainty, especially after the enactment of Law No. 19 of 2019 related to the CEC. Implications: This study emphasizes the importance of reconstructing authority through the revision of corruption eradication regulations and strengthening coordination and division of authority between law enforcement agencies so that the handling of corruption cases is more effective and synergistic. Novelty: The novelty of this research lies in the analysis of the imbalance of the authority of law enforcement agencies and the proposal of a model for the reconstruction of the authority of corruption law enforcement that supports the achievement of SDG 16.